Language board game: the adventure of Hang Nadim / Nur Aisha Hanina Khairul Nazmi and Sumayyah Shaidin - Khairul Nazmi, Nur Aisha Hanina; Shaidin, Sumayyah (Universiti Teknologi MARA, Kedah, 2023)
A board game is a fun game that can be played leisurely with our family and friends, engaging a player base from various ages to be involved in an active interaction and is very effective as an approach to educate in-class learning. The concept of the game is playing a board game that emphasizes language to expose the player to grammatical knowledge with inspiration from the local Malay folklore of ‘The Adventure of Hang Nadim’. This product would be suitable for English as Second Language (ESL) students as it can help them to experience and apply learning grammatical concept while also having fun playing games during their ample time. The use of a board game in an educational setting is preferable, as it serves both the purpose of entertainment and education. A fun learning environment, in theory, should promote a better learning experience overall. In this study, the pre-diploma students were required to fill out a pre-questionnaire about using a language board game as an educational learning tool in the classroom. Upon completion of the survey, this board game was tested among the pre-diploma students of UiTM Alor Gajah, Melaka, with a group of four players. A post-questionnaire was distributed to gather feedback on the board game after the test-run. Most ESL students who learn grammar in the classroom are struggling to grasp applying what they have learned. As a result, this language board game has the potential to be an effective educational tool for helping students in improving their grammatical skills.